2009
DOI: 10.1210/jc.2009-1029
|View full text |Cite
|
Sign up to set email alerts
|

TSPY1 Copy Number Variation Influences Spermatogenesis and Shows Differences among Y Lineages

Abstract: TSPY copy number variation significantly influences spermatogenic efficiency. Low TSPY1 copy number is a new risk factor for male infertility with potential clinical consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 27 publications
1
54
0
2
Order By: Relevance
“…Up to now only two CNVs have been correlated to infertility: i) AZFc gene dosage variation due to complete/partial removal or duplication of multicopy AZFc genes; ii) TSPY1 copy number variation on Yp. 78 Apart from few exceptions, such as central hypogonadism and some post-testicular forms, the only available treatment option for the large majority of male factor infertility is medically-assisted reproductive technology (ART), especially in vitro fertilization (IVF) or ICSI. 79,80 However, ART is a symptomatic therapy which does not address the underlying cause for infertility with the risk of transmitting both identified and not yet identified genetic anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now only two CNVs have been correlated to infertility: i) AZFc gene dosage variation due to complete/partial removal or duplication of multicopy AZFc genes; ii) TSPY1 copy number variation on Yp. 78 Apart from few exceptions, such as central hypogonadism and some post-testicular forms, the only available treatment option for the large majority of male factor infertility is medically-assisted reproductive technology (ART), especially in vitro fertilization (IVF) or ICSI. 79,80 However, ART is a symptomatic therapy which does not address the underlying cause for infertility with the risk of transmitting both identified and not yet identified genetic anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, crucial for a reliable analysis is the TSPY1 copy number variation susceptibility to stratification biases. As a matter of fact, significantly different means of TSPY1 copy number were found among different Y haplogroups (46,53), highlighting the importance of Y haplogroups-matching between cases and controls. The only available study to date in which cases and controls were matched for Y hgr distribution has been performed in the Italian population by our group.…”
Section: Tspy1 Arraymentioning
confidence: 95%
“…During the last years, Y-linked copy number variation analyses have been extended to the short arm of the Y chromosome which contains a TSPY1 gene array with variable number of TSPY1 copies (46,47). The TSPY1 belongs to a protein superfamily comprising SET and NAP, which are activating factors of the replication process.…”
Section: Tspy1 Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…The relative number of copies is higher in infertile men, with the exception of the AZFa deletion case 27 . Giachini et al 34 , found that the TSPY gene copy number affects spermatogenesis and that low copy number is a factor contributing to male infertility. On the other hand, Nickkholgh et al 35 argue that there is no correlation between impaired spermatogenesis and the TSPY gene copy number.…”
Section: Discussionmentioning
confidence: 99%